Librarian's perception of open access repository policy in Islamic State University Indonesia - Rodliyah, Ummi (Universitas Padjadjaran, 2023)
Institutional repositories that universities mostly manage have an important role in publishing academic works to the public. Some Islamic State University Indonesia, implementing the institutional open access repository policy. The purpose this research to know librarian’s perception of open access repository policy in Islamic State University Indonesia. This study used the mixed-method approach which were analyzed descriptively. Participants were determined by area sampling and divided into four groups as a representation of the Islamic State University area in Indonesia. Resource persons were 10% of participants selected from 416 Islamic State University librarians (42 people). Result study showed that repository access patterns comprised three categories: full open access 63%, 35% patterns were access parts of documents, and 2% access to abstract and metadata. The presentation pattern of the Islamic State University Indonesia, repository data was dominated by one full file open for access. Islamic State University Indonesia, librarians' perception of OAR was based on their understanding of the OAR definition. They agreed that, appropriately, OAR should be free of charge and be used for other legal purposes. However, there were many differences in understanding other aspects. The aspect of the most debate between them was the obligation to open all documents; 30% of participants from librarians disagreed on this aspect. The correlations between librarian perceptions and patterns of OAR are apparent from the results: 65% of librarians agree with OA, and 63% of repositories implement full OAR. Conclusion this research are librarians' perceptions influence the implementation of open access repository policies.